Kamisama kiss. Vol. 5 - Suzuki, Julietta (Shojo beat manga., 2011)
Nanami Momozono is homeless after her debt-ridden father skips town and the landlord kicks her out of their apartment. A man who she has saved from a dog attack offers his home, which turns out to be a shrine and Nanami finds herself worshiped as a deity!